2014
DOI: 10.1111/ijs.12373
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Susceptibility-Weighted Magnetic Resonance Sequences in the Visualization of Intravascular Thrombi in Acute Ischemic Stroke

Abstract: SWAN was more sensitive than T2* in the visualization of SVS in the intracranial arteries during the acute phase of ischemic stroke. Our study shows that the low number of SVS visualized using T2* in previous studies is probably related to a lack of sensitivity of the sequence, rather than to the nature or age of the thrombus. The greater sensitivity of SWAN seems to be linked to the visualization of SVS in cases of small thrombi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…As already mentioned, the sensitivity of T2* to detect acute intracranial thrombi is not perfect. 5,[10][11][12] This likely explains why 12 patients with arterial occlusion on admission MRA did not have SVS. Furthermore, SVS extension or regression might reflect structural or metabolic changes within the thrombus over time rather than true thrombus evolution, 15,16 which may explain why 10 patients had complete regression of SVS on follow-up MRI, despite persistent occlusion on MRA.…”
Section: February 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, the sensitivity of T2* to detect acute intracranial thrombi is not perfect. 5,[10][11][12] This likely explains why 12 patients with arterial occlusion on admission MRA did not have SVS. Furthermore, SVS extension or regression might reflect structural or metabolic changes within the thrombus over time rather than true thrombus evolution, 15,16 which may explain why 10 patients had complete regression of SVS on follow-up MRI, despite persistent occlusion on MRA.…”
Section: February 2017mentioning
confidence: 99%
“…Furthermore, SVS extension or regression might reflect structural or metabolic changes within the thrombus over time rather than true thrombus evolution, 15,16 which may explain why 10 patients had complete regression of SVS on follow-up MRI, despite persistent occlusion on MRA. Although some MR sequences, such as susceptibility-weighted imaging, are more sensitive than T2* for thrombus detection, 10,17,18 they are more timeconsuming and particularly their use in the hyperacute stroke setting is questionable. Lastly, the purposely devised assessment of SVS extension relied on qualitative, although expertbased, visual image analysis.…”
Section: February 2017mentioning
confidence: 99%
“…Although Allibert et al showed that the presence of an SVS in SWI was not associated with cardioembolism, 5 Horie et al showed that cardioembolic stroke was more frequently associated with the presence of an SVS in susceptibility weight angiography. 11 Our study, which analyzed the SVS quantitatively, showed that the increased SVS diameter was associated with cardioembolic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…5 For better use of this highly sensitive tool, we redefined the SVS as a hypointense signal independent of its size and quantitatively analyzed the SVS diameter and length in patients with acute ischemic stroke who underwent endovascular treatment. We assessed the correlation between the 2 SVS parameters and the stroke mechanism and that between the SVS volume and the recanalization status.…”
mentioning
confidence: 99%
“…For determining the site of occlusion, SWI exhibits better sensitivity and specificity than T2 gradient echo (Fig. 2) or 3D TOF imaging [17–19]. It is also much more effective in identifying distal thrombi, for both anterior [17, 20, 21] and posterior [19] localisations (Fig.…”
Section: Swi Sequencesmentioning
confidence: 99%